The Influence of Competence and Internal Control Systems on Village Government Accountability in Managing Village Funds: Case Study of Meteseh Village, Boja District - Dwi Laras Santi; Nanang Yusroni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
This study aims to determine the influence of apparatus competence, internal control systems, accountability on the management of village fund allocations with community participation as a moderator of village officials in the Mranggen District area. The research method used in this study was quantitative by distributing questionnaires to village apparatus respondents in the Meteseh village area, Boja sub-district. Accountability is an important thing for entities to have, both business and government entities, as a form of accountability to shareholders. The government is an organization whose job is to serve the community. In the private sector, accountability will appear automatically if an entity has issued or is in the process of issuing securities on the capital market and the entity controls assets in a fiduciary capacity for a large group of people.